Caring for elderly parents: Perceived filial obligations among Maghrebine immigrants in Italy. (December 2020) - Albertini, Marco; Semprebon, Michela
The migrant population in Southern European countries is aging. In the next future, long-term care needs of immigrant individuals will be a major issue in the evolution of social policies in these countries. In this context, it becomes important to examine what are the norms of filial obligations that govern the exchange of social support within migrant families. The study focuses on solidarity norms and support expectations among Mahgrebine immigrants living in Italy. It is shown that: i. intergenerational co-residence is seen as the best strategy to cope with the care need of elderly parents; ii. only a minority of respondents, especially those born in Italy or arrived before age 6, think that providing economic support or hiring a professional carer is a good solution. The importance of cultural and religious motivations at the basis of norms of filial obligations was explicitly, particularly as far as cohabitation is concerned. The majority of respondents held a gender-neutral view with respect to the sharing of responsibilities, although some gendered divisions emerged. Respondents who either were born in Italy or migrated before age six are considerably more likely to hold gender-neutral views on the division of informal care work.